Kebijakan Tentang Jumlah Siswa dan Keefektifan dalam Proses Pembelajaran - Ramedlon, Ramedlon; Sirajuddin, Sirajuddin; Zulkarnain, Zulkarnain; A.Suradi, A.Suradi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT The purpose of this research is to describe the importance of considering the capacity of the number of students in the learning process so that the learning process becomes effective. This study uses the literary method, by exploring theoretical studies and expert opinions and looking for literature reviews as material for analysis to draw conclusions. The conclusion of this study is that effective learning is a process of producing students' absorption of learning material and changes in student behavior that are useful for their lives. The success of learning is not only focused on student achievement academically which is symbolized by numbers but also concentrated on how to make students smart, well-behaved and broad-minded. The number of students can affect the task-oriented classroom climate, increase student participation in class, make it easier for teachers to monitor students and achieve learning goals properly and according to plan. Conclusion, an important factor in effective learning is class organization including the number of students in one class, a number that is too large is less effective in achieving learning goals. Keywords: number of students, effectiveness, learning